Institutional Capacity and Sustainability of Customary Forests: Customary Forest Management in Rantau Kermas Village - Lega, Michael; Wahid, Makmun; Darminto, Citra (Journal of Local Government Issues, 2024)
The urgency of managing natural resources, especially customary forests, is increasing along with climate change and environmental degradation, which threaten the sustainability of the global ecosystem. This research aims to investigate the role of customary forest management in maintaining environmental sustainability and the welfare of local communities while identifying institutional capacity to achieve these goals. This research involves an in-depth case study of the Customary Forest Management Group (KPHA) in Rantau Kermas Village. Data sources were obtained through interviews, documentation and observation. This study also utilized the Nvivo 12 Plus analysis tool to assist with data coding. This research reveals that effective customary forest management can maintain a balanced ecosystem, protect biodiversity, and provide economic benefits to local communities. Strengthening institutional capacity through community participation, strong regulations, and collaboration with various related parties is the key to achieving this goal. This research implies the importance of supporting and developing sustainable customary forest management practices and strengthening institutional capacity to ensure environmental sustainability and the welfare of local communities in the future.